2019
DOI: 10.1039/c9cp03012c
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling effects in confined gold nanoparticle hydrogenation catalysts

Abstract: H2 activation proceeds via homolytic activation over AuNPs confined in ionic liquid hybrid supports and display high kinetic isotope effects and convex curves in the Arrhenius plots, which suggests the possible involvement of a tunneling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Importantly, our experiments allow the direct observation of the effect of conning the active sites on the Arrhenius plot. 51 The reaction rates decrease, yet the slopes (i.e., the activation energies, Fig. 5, table inset) remain nearly identical in each case.…”
Section: Resultsmentioning
confidence: 83%
“…Importantly, our experiments allow the direct observation of the effect of conning the active sites on the Arrhenius plot. 51 The reaction rates decrease, yet the slopes (i.e., the activation energies, Fig. 5, table inset) remain nearly identical in each case.…”
Section: Resultsmentioning
confidence: 83%
“…From kinetic studies and the determination of kinetic isotopic effects, the authors concluded that the dynamic chemisorbed IL layers act as nanocontainers for the Au NPs and play a key role in controlling the mode of activation of H 2 (homolytic vs heterolytic). 38 …”
Section: Discussionmentioning
confidence: 99%
“…The same group investigated the potential of confinement effects in catalytic systems composed of Au NPs immobilized on Al 2 O 3 -based SILPs in the hydrogenation of trans -cinnamaldehyde. From kinetic studies and the determination of kinetic isotopic effects, the authors concluded that the dynamic chemisorbed IL layers act as nanocontainers for the Au NPs and play a key role in controlling the mode of activation of H 2 (homolytic vs heterolytic) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are supported by several theoretical and experimental studies. 380,384 For example, the hydrogenation of benzene by bimetallic Ru@Pt NPs in [C 4 C 1 Im][PF 6 ]/hydrocarbon leads to the isolation of 1,3-cyclohexadiene in relatively high selectivity (21%) at low substrate conversion (5%). These results suggest that metal NPs in highly organized ILs can operate far from equilibrium.…”
Section: The Il-effect In Catalysismentioning
confidence: 99%